A novel approach toward Snowman-like polymer/SiO2 hybrid nanoparticles via gas-driving. Issue 22 (19th February 2020) - Lin, Qianqian; Wang, Juan; Yuan, Jinfeng; Jiang, Yuan; Zhu, Lei; Pan, Mingwang
Abstract : For the first time, we report an interesting transition from conventional core–shell polymer/SiO2 particles to self-stable snowman-like particles, which can be achieved by adding a low-boiling point oil-soluble monomer. Abstract : For the first time, we report an interesting transition from conventional core–shell polymer/SiO2 particles to self-stable snowman-like particles, which can be achieved by adding a low-boiling point oil-soluble monomer because the volatile monomer not only plays a lubrication role, but also acts as a gas "motor" to drive the silica precursor polycondensate migration.